Comparative characterization of Leporipoxvirus members’ reproduction in continuous cell culture - O. G. Lapteva; S. G. Yurkov; I. P. Sindryakova; A. V. Lunitsin (Ветеринария сегодня)
Examination of the virus-cell interactions is of both scientific and practical importance. Our study was aimed at comparative characterization of rabbit myxoma virus and Shope fibroma virus biological properties that manifested during the virus reproduction in RK-13/2-03 clonal continuous rabbit kidney cell culture. It was demonstrated that the viruses varied in infection development and cytopathic effect duration in RK-13/2-03 cell culture. Apparent lesions in cell monolayers infected by myxoma virus and fibroma virus at similar multiplicity of infection and cultivation temperature were observed on day 2 and day 3 of cultivation, respec- tively, as well as maximum cell lesions with evident degeneration were observed on day 3 and day 6 of cultivation, respectively. Myxoma virus was accumulated at titre of 6.25–6.50 lg TCID50/0,2 cm3, and Shope fibroma virusа was accumulated at titre of 5.50−5.75 lg TCID50/0.2 cm3. Shope fibroma virus demonstrated such infectivity during three passages and myxoma virus demonstrated such infectivity during twenty passages. Prepared cultures were identified as myxoma virus and Shope fibroma virus with molecular genetic analysis. Tests of the viruses for their antigenic relatedness showed that antibodies against myxoma virus were able to neutralize Shope fibroma virus also. NT titres of antibodies against both viruses were similar (1:8). RK-13/2-03 cell culture was found to be highly permissive to Shope fibroma virus that had been isolated from the diseased rabbit and not been an attenuated variant.